Evaluate
cos 7 π − cos 7 2 π + cos 7 3 π .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
does this really need to get that complicated...
"7th root of unity"? "Real parts"? Pretend that your audience is not composed solely of mathematicians. What are you saying?
Log in to reply
the solution presented here makes sense. He is using Demoivre's theorem in the first line.
Log in to reply
Yes, it makes sense to a mathematician, but that's not what he's asking for. I agree, having limited knowledge of theorems and proofs that it would be nice to derive answers from first principles instead of having a repository of prior knowledge of algorithms and equations that I can just plug a solution into. Every answer I've found for every problem I've answered I had to work through without a knowledge of mathematical vocabulary-- and I understand why the vocabulary is important, but more important than that is an intuition. I think when non-mathematicians are looking for "how to solve" a problem, they want help with the intuition.
Try reading the lesson???
I'd rather use ω 7 − 1 = 0 , then by Vieta's Formula we'd get the sum of roots, which is 0 . Now, since the roots form a regular heptagon on Argand-Gauss plan, we can use symmetry in order to say that R e { ∑ i : e v e n ω i } = R e { ∑ j : o d d ω j } .
Perfect resolution!! I did cos(pi/7)-cos(2pi/7)+cos(3pi/7)=Re(cis(pi/7)+cis(3pi/7)+cis(5pi/7))=Re(cis(x)+cis³(x)+cis^5(x))=Re(cis(x)(cis(6x)-1)/(cis(2x)-1))= Re(cis(x)2isen(3x)cis(3x)/2isen(x)cis(x))=2sen(3x)cos(3x)/2sen(x)= 1/2 * sen(6x)/sen(x)= 1/2 * sen(6pi/7)/sen(pi/7)=1/2 and the work was big :S
plz post one easy solution
Let x = Pi/7
Then 7 x = Pi , cos 2 x = - cos 5 x
Then the L.H.S = M = cos x + cos 3 x + cos 5 x
Multiply both sides by 2 sin x
Then we have
2 M sin x = 2 sin x cos x + 2 sin x cos 3 x + 2 sin x cos 5 x
Using the identity :
sin (x + y) + sin (x - y) = 2 sin x cos y
Then
2 M sin x = sin 2 x + sin 4 x - sin 2 x + sin 6 x - sin 4 x
2 M sin x = sin 6 x = sin (7 x - x) = sin (PI - x) = sin x
Then
M = 1/2
For the benefit of some readers, I will write up a solution that does not explicitly refer to roots of unity.
Since the points ( cos 7 k π , sin 7 k π ) , for odd k , are equally spaced on the unit circle, forming a regular heptagon, the sum of their coordinates is 0, by symmetry(sketch this heptagon to better understand the solution!). Thus the sum of all cos 7 k π is 0, where k runs through all odd integers from 1 through 13. For k = 7 we get cos π = − 1 . Now the sum for k = 9 , 1 1 , 1 3 is the same as for k = 1 , 3 , 5 , for example, cos 7 1 1 π = cos 7 3 π (the heptagon is symmetric with respect to the x-axis). Thus 2 cos 7 π + 2 cos 7 3 π + 2 cos 7 5 π − 1 = 0 . Since cos 7 2 π = − cos 7 5 π , we have cos 7 π − cos 7 2 π + cos 7 3 π = cos 7 π + cos 7 3 π + cos 7 5 π = 2 1 .
Let x = Pi/7
Then 7 x = Pi , cos 2 x = - cos 5 x
Then the L.H.S = M = cos x + cos 3 x + cos 5 x
Multiply both sides by 2 sin x
Then we have
2 M sin x = 2 sin x cos x + 2 sin x cos 3 x + 2 sin x cos 5 x
Using the identity :
sin (x + y) + sin (x - y) = 2 sin x cos y
Then
2 M sin x = sin 2 x + sin 4 x - sin 2 x + sin 6 x - sin 4 x
2 M sin x = sin 6 x = sin (7 x - x) = sin (PI - x) = sin x
Then
M = 1/2
Solution using complex numbers.
We know that c o s ( 7 2 π ) = − c o s ( 7 5 π )
Therefore, S = c o s ( 7 π ) + c o s ( 7 3 π ) + c o s ( 7 5 π )
Take the following complex number: z = c i s ( 7 π )
By De Moivre's formula: z 7 = c i s ( π ) = − 1 .......... Equation 1
As z is not 1, we can factor this as:
z 6 − z 5 + z 4 − z 3 + z 2 − z + 1 = 0 .......... Equation 2
Using the relation between cis and cos:
z + z − 1 = 2 c o s ( 7 π )
z 3 + z − 3 = 2 c o s ( 7 3 π )
z 5 + z − 5 = 2 c o s ( 7 5 π )
Adding the expressions above:
z + z − 1 + z 3 + z − 3 + z 5 + z − 5 = 2 S
Using equation 1: z − 1 = − z 6 and z − 3 = − z 4 and z − 5 = − z 2
Therefore,
z − z 6 + z 3 − z 4 + z 5 − z 2 = 2 S
Using equation 2: 2S=1
S = 2 1
use cos2x and cos3x expansions...that is c o s 2 x − s i n 2 x and 4 c o s 3 x − 3 c o s x
Always leave your audience guessing...
cos (180/7) -cos(360/7) +cos (540/7) = 1/2
use pi = 180 ; then you can replace the values :
180x1=180
180x 2 = 360
180 x 3 = 540
cos (pi/7) - cos (2pi/7) + cos (3pi/7)= 2 cos (2pi/7) cos (pi/7) - cos (2pi/7) = cos (2pi/7) (2cos pi/7 - 1) = cos (2pi/7) (-2 cos 6pi/7 -1) = cos (2pi/7) (4 sin^{2} (3pi/7) - 3) = cos (2pi/7) [-sin (9pi/7)]/ sin (3pi/7) = cos (2pi/7) sin (2pi/7)/sin (3pi/7) = (1/2) (sin 4pi/7)/sin (3pi/7) = 1/2.
Let x = Pi/7
Then 7 x = Pi , cos 2 x = - cos 5 x
Then the L.H.S = M = cos x + cos 3 x + cos 5 x
Multiply both sides by 2 sin x
Then we have
2 M sin x = 2 sin x cos x + 2 sin x cos 3 x + 2 sin x cos 5 x
Using the identity :
sin (x + y) + sin (x - y) = 2 sin x cos y
Then
2 M sin x = sin 2 x + sin 4 x - sin 2 x + sin 6 x - sin 4 x
2 M sin x = sin 6 x = sin (7 x - x) = sin (PI - x) = sin x
Then
M = 1/2
Problem Loading...
Note Loading...
Set Loading...
Let ω = cos 7 2 π + i sin 7 2 π be the 7 t h root of unity.
Hence, 1 + ω + ω 2 + . . . . + ω 6 = 0 .Comparing the real parts, we have
1 + cos 7 2 π + cos 7 4 π + cos 7 6 π + cos 7 8 π + cos 7 1 0 π + cos 7 1 2 π = 0 .
Using cos θ = − cos ( π − θ ) = − cos ( θ − π ) ,we have,
2 ( cos 7 π − cos 7 2 π + cos 7 3 π ) = 1